Mobile Phone Security and Forensics A Practical Approach - Androulidakis, Iosif I.; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Mobile Phone Security and Forensics provides both theoretical and practical background of security and forensics for mobile phones. The author discusses confidentiality, integrity, and availability threats in mobile telephones to provide background for the rest of the book. Security and secrets of mobile phones are discussed including software and hardware interception, fraud and other malicious techniques used (3z(Bagainst(3y (Busers. The purpose of this book is to raise user awareness in regards to security and privacy threats present in the use of mobile phones while readers will also learn where forensics data reside in the mobile phone and the network and how to conduct a relevant analysis.s
Introduction -- Confidentiality -- Integrity and Availability Threats in Mobile Phones -- A multinational survey on users$1 (Bpractices, perceptions and awareness regarding mobile phone security -- Voice, SMS and identification data interception in GSM -- Software and Hardware Mobile phone tricks -- SMS security issues -- Mobile Phone Forensics -- Conclusion.s
Keywords: Engineering; Forensic medicine; Data protection; Telecommunication; Engineering; Communications Engineering, Networks; Systems and Data Security; Security Science and Technology; Forensic Science